The consumer experience in Piura: Analysis of the Experiential Marketing resources in modern retail stores of clothing and footwear - Arbaiza Rodríguez, Francisco (2019)
In recent years, studies of consumer behavior have focused on demonstrating that individuals value the experience of consumption. Given this reality, the experiential marketing formula has managed to solve this need by proposing actions that generate consumer experience and maximize the value of products and services allowing the consumer to establish an emotional, rational or sensory connection with brands during the purchase process. This article is an analysis of the marketing experiences offered by retailers of clothing and footwear from major shopping centers in Piura. The objective of this work is to define the experiential formula offered by each store of modern retail of the two main shopping centers and determine wich stores give importance to the consumer experience.